Pengolahan Daun Bayam Hijau (Amarhantus tricolor) guna Meningkatkan Tingkat Konsumsi Masyarakat - Qadri, Sri Nur; Yunus, Yusdalifa Ekayanti; Yamin, Mayasari; Tawakkal Gau, Andi Dita; Zamzam, Syamsiar (Universitas Muhammadiyah Sidenreng Rappang, 2022)
Green spinach is a vegetable that can be consumed by its leaves as a green vegetable and can be used as a processed food, both as a main menu and as a processed snack. Spinach has many nutritional contents such as protein, minerals, calcium, iron and vitamins needed in the body. Iron contained in the supplement, if consumed in large doses and a long time can cause damage to the intestinal lining, abnormalities in the pH of the body, shock and liver failure. An alternative to meet iron needs can be done by consuming vegetables that contain iron, including green spinach. The purpose of community service is to provide education to the public about the content of green spinach and the processing of green spinach so that it can increase the level of public consumption. This service applies counseling methods related to spinach processing from theory to manufacturing practice. The results achieved are that the public knows about the benefits and content of green spinach which is indispensable for the body and how to process spinach leaves into spinach chips into snacks that children like because this spinach chip snack is not only delicious but also has high nutritional value.